THE ADVENTURES OF TOM SAWYER - TWAIN, MARK (The Macmillan Press London, 1979)
Satirical and nostalgic, Mark Twain$1 (Bs epic masterpiece, the Adventures of Tom Sawyer, brings out the inequities of adult reality from beneath the innocence of childhood. In the fictional town of St. Petersburg, Missouri, along the Mississippi River, Tom Sawyer lives with his Aunt Polly and half-brother Sid. As the novel begins, we catch him stealing from the jam jar and narrowly escaping being hit. But his life is full of adventurous episodes. What happens as he moves from one escapade to another$1 (Baccompanying Huckleberry Finn to the graveyard at night where they witness a trio of grave robbers; falling in love with Becky Thatcher and being shunned; enjoying the new found freedom and then being struck by the idea of appearing at his own funeral; hunting for buried treasure in a haunted house with Huck and so on..s
Keywords: English Literature; English Fiction; Missouri; Runaway Children